Housing Careers, Intergenerational Support and Family Relations - Lennartz , Christian; Ronald, Richard (Taylor & Francis, 2019)
In this comprehensive volume, authors from across the social sciences explore how housing wealth transfers have impacted the integration of families, society and the economy, with a focus on the (re)negotiation of the 'generational contract'. While housing has always been central to the realization and reproduction of families, more recently, the mutual embedding of home and family has become more obvious as realignments in housing markets, employment and welfare states have worked together to undermine housing access for new households, enhancing intergenerational interdependencies. More families have thus become involved in smoothening the routes of younger adult members into and up the 'housing ladder'. While intergenerational support appears to have become much more widespread, it remains highly differentiated across countries, cities and regions, as well as uneven between social and income classes. This book addresses the increasing role that family support, and intergenerational transfers in particular, are playing in sustaining the formation of new households and the transition of young adults towards social and economic autonomy. The authors draw on diverse international cases and a variety of methodologies in order to advance our understanding of housing as a key driver of contemporary social relations and inequalities. This book was originally published as a special issue of the journal Housing Studies. Chapters 1, 6, 8 and 9 are available Open Access at https://www.routledge.com/products/ 9780367262822.